Sorting Nexin 10 as a Key Regulator of Membrane Trafficking in Bone-Resorbing Osteoclasts: Lessons Learned From Osteopetrosis - Elson, Ari; Stein, Merle; Rabie, Grace; Barnea-Zohar, Maayan; Winograd-Katz, Sabina; Reuven, Nina; Shalev, Moran; Sekeres, Juraj; Kanaan, Moien; Tuckermann, Jan; Geiger, Benjamin (Frontiers in Cell and Developmental Biology, 2021)
Bone homeostasis is a complex, multi-step process, which is based primarily on a tightly orchestrated interplay between bone formation and bone resorption that is executed by osteoblasts and osteoclasts (OCLs), respectively. The essential physiological balance between these cells is maintained and controlled at multiple levels, ranging from regulated gene expression to endocrine signals, yet the underlying cellular and molecular mechanisms are still poorly understood. One approach for deciphering the mechanisms that regulate bone homeostasis is the characterization of relevant pathological states in which this balance is disturbed. In this article we describe one such “error of nature,” namely the development of acute recessive osteopetrosis (ARO) in humans that is caused by mutations in sorting nexin 10 (SNX10) that affect OCL functioning. We hypothesize here that, by virtue of its specific roles in vesicular trafficking, SNX10 serves as a key selective regulator of the composition of diverse membrane compartments in OCLs, thereby affecting critical processes in the sequence of events that link the plasma membrane with formation of the ruffled border and with extracellular acidification. As a result, SNX10 determines multiple features of these cells either directly or, as in regulation of cell-cell fusion, indirectly. This hypothesis is further supported by the similarities between the cellular defects observed in OCLs form various models of ARO, induced by mutations in SNX10 and in other genes, which suggest that mutations in the known ARO-associated genes act by disrupting the same plasma membrane-to-ruffled border axis, albeit to different degrees. In this article, we describe the population genetics and spread of the original arginine-to-glutamine mutation at position 51 (R51Q) in SNX10 in the Palestinian community. We further review recent studies, conducted in animal and cellular model systems, that highlight the essential roles of SNX10 in critical membrane functions in OCLs, and discuss possible future research directions that are needed for challenging or substantiating our hypothesis.